2006
DOI: 10.1089/tmj.2006.12.663
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Quality of Life of Children and Parents During Their Tele-HomeCare Experience

Abstract: Video-conferencing and remote vital signs monitors were used to provide Tele-HomeCare (THC) to children with complex healthcare needs. This paper reports the effects of THC on the health-related quality of life (QoL) of children and their parents, and the Impact on Families (IoF). A total of 63 children and their parents were enrolled in a THC trial in which they received traditional home care services and up to 6 weeks of THC. A reference group of 16 children and their parents was also recruited and received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Oliver concluded that it appeared that the technology was seen as a burden at this time by family members. This adds weight to the concept discussed by Young [11] that video consultations may reach a threshold where their usefulness ceases.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Oliver concluded that it appeared that the technology was seen as a burden at this time by family members. This adds weight to the concept discussed by Young [11] that video consultations may reach a threshold where their usefulness ceases.…”
Section: Resultsmentioning
confidence: 94%
“…Five studies, including Morgan et al [3], Young et al [11], Laila et al [13], Hebert et al [42] and Demiris et al [28] examined the effect of home telehealth via video-consultation on quality of life and in particular, anxiety for families caring at home. Morgan and colleagues [3] focussed on children with congenital heart disease post-discharge from hospital and compared outcomes of telephone contact only with using home telehealth .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the realities of some contexts can make this ideal impracticable, eight examples of researchers using phased approaches (featuring multiple related studies) to development and evaluation of their interventions were found here [8,10,18,21,25,30,65,66,77,78,92-94,102-105,108,109]. …”
Section: Discussionmentioning
confidence: 99%